PB.06 Supporting early breast milk expression in the Neonatal Unit – are we doing enough?. (9th June 2014) - Oliveira, V; Angel, J; Tavener, K; Hickey, A
Abstract : Background and aims: When breastfeeding gets delayed, prompt breast-milk expression facilitates establishment and maintenance of lactation. On neonatal units, the recommended UNICEF target of all mothers achieving early milk expression within 6 h of birth is often not achieved. For critically ill infants, breast milk is particularly beneficial due to its nutritional and immunological benefits. clinical practices that positively affect timely initiation are poorly described. our aim was to investigate these practices. Methods: A cross-sectional survey was performed on a tertiary neonatal unit to assess lactation and breastfeeding support provided to mothers of term and preterm infants. anonymous questionnaires were distributed, between days 3–7 postpartum. Results: Of 79 participants, 53% were advised about breast-milk antenatally. Overall, 90% of mothers were helped to hand-express but only 11% within 6 h of birth. Breastfeeding nurses and midwives provided most advice but neonatal nurses were involved in only 10% of episodes. The likelihood of early expression was lower for mothers of preterm infants and in mothers who had not done kangaroo care but not significantly. Maternal perception of support was positive in 90% of cases. Conclusion: The survey demonstrated a large discrepancy between recommended levels of support and actual practice. questions about the feasibility of Unicef recommendations in neonatal units remain. Further analysis of the factors that impeded early expression is needed. It may well be that in mothers whose infants require neonatal care, there are entirely valid reasons for some delay in initiation of expression.